Research Productivity among Faculty Members of the University of Cebu, Philippines - Etcuban, Jonathan; Andrin, Glenn; Ninal, Melvin; Campanilla, Bell; Dinauanao, Aahron; Macugay, Philip Joel; Belarmino, Gwen (JPAIR Institutional Research, 2016)
Research is the heart of every higher education institution (HEI). Universities are coming under enormous strength to boost the productivity of faculty research to meet the ASEAN integration. The accrediting agency assures that instructions and community extensions are research-based. This study assessed the research productivity of teachers at the University of Cebu, Philippines. Based on the gathered data, a University Research Portfolio was proposed to serve as a guide for the administrators to increase production of teachers in the context of a research project, presentation, and publications. The study used a descriptive correlational method with the aid of a researcher-made questionnaire. There were 171 college teachers who were used as respondents of the study. The accumulated data were analyzed, and interpreted using simple percentage, weighted mean, Chi-square test of independence and ANOVA. Results showed that most of the teachers have low research productivity and that they need training in research methods and statistics. It was concluded that college teachers had limited financial assistance and cash incentives that the University offers to them. The researchers strongly recommend that the proposed University Research Portfolio be used. However, further research on its effectiveness should be carried out to confirm the preliminary findings.